Determinant of Sustainability Performance: Diversification, Corporate Governance And Intellectual Capital - Asih Handayani; Ratih Qadarti Anjilni (Journal of Applied Accounting and Taxation, 2024)
This study examines whether diversification impacts good corporate governance proxied by the board of directors, independent commissioners, audit committees, institutional ownership, and intellectual capital on sustainability performance. This research explores previous studies regarding sustainability performance. This study uses LQ45 index companies as a research sample in the 2020-2022 period. The researchers used a purposive sampling method to select 22 companies that met the criteria. The analytical method used is Panel Data Regression Analysis. The results of the study show that independent commissioners and intellectual capital have a significant effect on sustainability performance. At the same time, diversification, board of directors, audit committees, and institutional ownership do not affect sustainability performance.